Determinar la influencia de las ametropía en el aprendizaje perceptivo en escolares que asisten a Óptica “Optivity", El Empalme -Guayas. Diciembre 2022 - mayo 2023. - Vera Álava, Andrea Belén (2023)
Vision is a fundamental sense for learning and perception. When children have uncorrected ametropia, their ability to process and understand visual information is affected, they may have difficulties performing actions such as reading or focusing attention on objects or didactic material. These difficulties cause children to get tired. headaches faster and in some cases feel discouraged when it comes to learning. The objective of this study is to determine the influence between ametropia and perceptual learning in school patients who attend the OPTIVITY optician in the canton of El Empalme - Guayas - Ecuador in the period December 2022 - May 2023. In the present research work, a descriptive, quantitative and qualitative methodology was applied. It is a non-experimental cross-sectional study. In the results it was obtained that 93% of the parents stated that before implementing a visual treatment their children presented difficulties during the learning process. The main ametropia detected is myopia with 45.1% followed by astigmatism with 28.4 and finally hyperopia with 26.5%. 67.6% of parents stated that they will take their children's eye exams annually. Myopia is the main ametropia detected in this study, it is also concluded that there is a relationship between ametropia and academic performance since those patients who implemented an optical correction improved their grades, it is necessary to implement routine optometric check-ups in schools because ametropia Undetected affect the academic development of students. In addition, the earlier the detection of ametropias, the treatment provides better results.